2022
DOI: 10.1093/stcltm/szac063
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Amniotic Fluid Stem Cell Extracellular Vesicles Promotes Fetal Lung Branching and Cell Differentiation at Canalicular and Saccular Stages in Experimental Pulmonary Hypoplasia Secondary to Congenital Diaphragmatic Hernia

Abstract: Pulmonary hypoplasia secondary to congenital diaphragmatic hernia (CDH) is characterized by impaired branching morphogenesis and differentiation. We have previously demonstrated that administration of extracellular vesicles derived from rat amniotic fluid stem cells (AFSC-EVs) rescues development of hypoplastic lungs at the pseudoglandular and alveolar stages in rodent models of CDH. Herein, we tested whether AFSC-EVs exert their regenerative effects at the canalicular and saccular stages, as these are transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…We have previously shown that AFSC-EVs restore fetal lung branching morphogenesis and epithelial cell differentiation in rodents and human models of CDH [20][21][22] . The current study provides evidence that AFSC-EV administration to rat and human compressed fetal lungs rescues also fetal lung vascular development.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously shown that AFSC-EVs restore fetal lung branching morphogenesis and epithelial cell differentiation in rodents and human models of CDH [20][21][22] . The current study provides evidence that AFSC-EV administration to rat and human compressed fetal lungs rescues also fetal lung vascular development.…”
Section: Discussionmentioning
confidence: 98%
“…The multifactorial pathogenesis of arrested lung development in CDH necessitates an antenatal therapy that addresses all aspects of impaired fetal lung growth, maturation, and vascularization 8 . We have previously shown that AFSC-EVs restore fetal lung branching morphogenesis and epithelial cell differentiation in rodents and human models of CDH 20-22 . The current study provides evidence that AFSC-EV administration to rat and human compressed fetal lungs rescues also fetal lung vascular development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This timeline is further shortened by the fact that AF / chorionic villi sampling is not normally performed until the end of the first trimester; and furthermore, the majority of prenatal therapies are currently ideally delivered prior to 30 weeks. Several examples of iPSCs-organoid derivation highlight the need of at least 21 weeks to produce the organoids 73 . Our approach benefits from the already committed progenitors present in the fetal fluids, which require minimal manipulation to lead to the production of a large amount of primary autologous fetal organoids in approximately 4 to 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative therapies, such as stem cell-based approaches, are another prospective area for therapeutic development. These novel treatments could lung tissue damage incurred by fetal lung development disorders and promote lung regeneration, a concept backed by emerging preclinical and clinical studies demonstrating the potential benefits of stem cell therapies for lung diseases [238][239][240].…”
Section: Exploring Future Research Directions In the Domain Of Fetal ...mentioning
confidence: 99%